Comparative Analysis of Functional Outcomes: Extramedullary Versus Intramedullary Fixation in Unstable Inter-Trochanteric Femoral Fractures: Extramedullary Versus Intramedullary Fixation - Bhatti, Rasheed Ahmed; Mirjat, Ashfaque Hussain; Abro, Awais; Maheshwari, Lachman Das; Hussain, Agha Mahtab; Memon, Faisal (Pakistan Journal of Health Sciences, 2024)
Unstable trochanteric femoral fractures are challenging to manage. Two options exist for the operative treatment and management of unstable trochanteric fractures; i.e. extramedullary or intramedullary stabilization. However, there is a dearth of good evidence of the clinical efficacy of either of the two methods especially in terms of functional outcomes. Objective: To compare the functional outcome following fixation of unstable trochanteric femoral fractures via extramedullary versus intramedullary methods. Methods: This prospective cohort was conducted upon 46 adult patients and admitted at Liaquat University Hospital Hyderabad/Jamshoro, after taking written informed consent from parents. Functional outcomes utilizing the Timed Up and Go Test and Harris Hip Score, at 3 months and 6 months post-surgery and radiographic parameters were gathered to evaluate heterotopic ossification and femoral neck shortening at follow-up visits using a pre-structured questionnaire. The data was analyzed with SPSS V.21 and Microsoft Excel 2016. Results: The sample predominantly consisted of males, with a mean age of 31 ± 5 years. Intramedullary fixation showed superior early mobility outcomes and maintained better hip function scores compared to extramedullary fixation for unstable inter-trochanteric femoral fractures. Intramedullary fixation also demonstrated lower rates of heterotopic ossification and less femoral neck shortening, indicating potential benefits in reducing complications and preserving anatomical integrity. Conclusions: In conclusion, the study findings suggest intramedullary fixation as a favorable option for optimizing functional recovery and radiographic outcomes in such fractures